Breaking the strength-ductility paradox in advanced nanostructured Fe-based alloys through combined Cu and Mn additions. (September 2020) - Kong, H.J.; Yang, T.; Chen, R.; Yue, S.Q.; Zhang, T.L.; Cao, B.X.; Wang, C.; Liu, W.H.; Luan, J.H.; Jiao, Z.B.; Zhou, B.W.; Meng, L.G.; et al.
Abstract: The strength-ductility paradox is a long-sought challenge for all engineering materials. In this study, we escaped the strength-ductility trade-off by engineering nano-scale heterogeneities carefully in the advanced nanostructured Fe-based alloys through alloying with Cu and Mn additions. We demonstrated a triple ductility enhancement by 20% together with a strength improvement of 100MPa compared to the alloys with sole Cu additions, overturning a common understanding of the strength-ductility trade-off. The strength-ductility enhancement is attributed to the complex interplay between the transformation induced plasticity (TRIP) and the coherent nano-scale Cu precipitates as well as the resultant heterogeneous stress–strain partitioning and dislocation interactions. Graphical abstract: Image, graphical abstract